Interlinkages between bacterial populations dynamics and the operational parameters in a moving bed membrane bioreactor treating urban sewage. (1st January 2016) - Reboleiro-Rivas, P.; Martín-Pascual, J.; Morillo, J.A.; Juárez-Jiménez, B.; Poyatos, J.M.; Rodelas, B.; González-López, J.
Abstract: Bacteria are key players in biological wastewater treatments (WWTs), thus a firm knowledge of the bacterial population dynamics is crucial to understand environmental/operational factors affecting the efficiency and stability of the biological depuration process. Unfortunately, little is known about the microbial ecology of the advanced biological WWTs combining suspended biomass (SB) and attached biofilms (AB). This study explored in depth the bacterial community structure and population dynamics in each biomass fraction from a pilot-scale moving bed membrane bioreactor (MBMBR) treating municipal sewage, by means of temperature-gradient gel electrophoresis (TGGE) and 454-pyrosequencing. Eight experimental phases were conducted, combining different carrier filling ratios, hydraulic retention times and concentrations of mixed liquor total suspended solids. The bacterial community, dominated by Proteobacteria (20.9–53.8%) and Actinobacteria (20.6–57.6%), was very similar in both biomass fractions and able to maintain its functional stability under all the operating conditions, ensuring a successful and steady depuration process. Multivariate statistical analysis demonstrated that solids concentration, carrier filling ratio, temperature and organic matter concentration in the influent were the significant factors explaining population dynamics. Bacterial diversity increased as carrier filling ratio increased (from 20% to 35%, v/v), and solids concentration was the main factor triggering the shifts of the community structure. These findings provide new insights on the influence of operational parameters on the biology of the innovative MBMBRs. Graphical abstract: Highlights: Bacterial populations dynamics were analyzed in a moving bed membrane bioreactor. Bacterial community was investigated by means of TGGE & 454-pyrosequencing. Suspended biomass & attached biofilm showed similar diversity profiles. Multivariate analysis linked community structure shifts to operating variables. Solids concentration was the main factor explaining populations dynamics.